Analysis Of Fire And Rescue Service Coverage In Surabaya City - Amanda Fharadita Olivia Rakhmad, (International Journal Of Health Science, 2025)
In addition to the spatial analysis, this study also considered the implications of population density and urban development patterns on the effectiveness of fire and rescue services. Sub-districts with high population densities and complex road networks, such as Rungkut and Dukuh Pakis, were particularly vulnerable due to delays in response time caused by traffic congestion and narrow street access. Furthermore, newly developed residential and industrial zones, particularly in the outskirts like Benowo and Pakal, showed inadequate emergency coverage due to the lack of nearby fire stations and limited road connectivity. The study underscores the importance of incorporating demographic and infrastructural data into emergency planning. Fire service planning that solely relies on theoretical models such as circular buffer zones tends to overlook the real-world constraints posed by road networks, traffic conditions, and topographic barriers. As a result, relying on network-based service area analysis provides a more realistic and operationally relevant perspective for decision-making. To enhance coverage, the study recommends optimizing station placement through Geographic Information System (GIS)-based modeling that factors in dynamic urban growth, accessibility, and service demand projections. Establishing satellite fire stations or deploying mobile fire units in the underserved sub-districts could be effective interim solutions while longer-term infrastructure developments are underway. Moreover, collaboration between fire departments, urban planners, and transportation authorities is essential to integrate fire safety considerations into city planning processes. By doing so, Surabaya can not only improve its emergency response performance but also build urban resilience in the face of increasing fire risks due to climate change and urban expansion.